Hydrothermal intercalation for the synthesis of novel three-dimensional hierarchically superstructured carbons composed of graphene-like ultrathin nanosheets. (May 2021) - Li, Zhaopeng; Yu, Peifeng; Zhong, Weihao; Zhang, Minglu; Li, Zhenghui; Cheng, Ao; Liang, Yeru; Miao, Lei; Yang, Xiaoqing; Zhang, Haiyan
Abstract: Hierarchical superstructured carbons (HSCs) assembled by low-dimensional fibers or sheets have held a great prospect in energy applications on account of their stable intersecting carbon network, large accessible surface area and optimized ion transfer. However, the synthesis of HSCs with well-defined nanostructure is still a challenge. Herein, a novel HSC is developed on the basis of constructing sandwich-type alternate layered carbon/Zn2 SiO4 composite by an intercalation growth strategy. This type of HSC is assembled by graphene-like ultrathin carbon nanosheets with a thickness less than 1 nm (2–3 carbon layers), and displays rigid and stable 3D network owing to the interconnected self-supported nanosheets. The in-depth investigation reveals that the growth of HSC complies with a unique "octopus model", and both the homogeneous and heterogeneous reaction conditions are applicable for the synthesis system. More importantly, the as-constructed superstructure can be coated on the surface of any SiO2 -containing substrates, which offers an avenue to design superstructured carbons with various morphologies. With combination of the large accessible surface area and optimized nanostructure for ion transfer and electron immigration, the as-prepared HSC demonstrates superior performance in electronic double-layer capacitor. Graphical abstract: Image 1 Highlights: Hydrothermal intercalation is developed to fabricate HSC. HSC is composed of graphene-like nanosheets and presents 3D intersecting structure. The growth of HSC follows a "octopus" model. HSC is able to be coated on SiO2 -containing substrate. HSC exhibits superior supercapacitive performance.